PROFESSIONAL DEVELOPMENT OF EMPLOYEES OF THE UNIVERSITY LIBRARIES AS A PART OF PERSONNEL MANAGEMENT - Shakula, Alla P. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article is devoted to the analysis of professional development system of employees of Mariupol State University Scientific Library, as part of its human resource management. It was determined the method and new forms of enhancing the professional development of employees.